The Influence of the SAVI Model on Students’ Motivation and Learning Outcomes in Social Studies at Madrasah Tsanawiyah - Renata Tiand Indriansyah; Saiful Amin (SAINTIS Publishing, 2025)
The study aims to (1) analyze the effect of the SAVI (Somatic, Auditory, Visualization, Intellectual) model on students’ motivation and (2) analyze the effect of the SAVI model on social studies learning outcomes. This research employs a quantitative approach with a quasi-experimental non-equivalent control group design. The subjects of the study were 49 eighth-grade students at MTs Almaarif 02 Singosari Malang, consisting of 25 students in the experimental class and 24 students in the control class. The experimental class received instruction using the SAVI learning model, while the control class was taught using the lecture method. Data were collected through motivation questionnaires and learning outcome tests. Statistical analysis was conducted using normality tests, homogeneity tests, and N-Gain tests to measure learning improvement. The results indicate that: (1) the SAVI learning model positively influences students' learning motivation, as they became more active and demonstrated greater enthusiasm in the learning process and (2) the SAVI learning model significantly improves students' learning outcomes compared to conventional methods, as evidenced by increased comprehension and academic achievement. Based on these findings, it is recommended that teachers implement the SAVI learning model as an innovative strategy to enhance students' motivation and learning outcomes. Future research can explore the effectiveness of this model across different subjects and educational levels.